2014
DOI: 10.1080/10376178.2014.11081929
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tai chi and yoga on balance and falls in a residential care setting: A randomised controlled trial

Abstract: Falls amongst older people is a global public health concern. Whilst falling is not a typical feature of ageing, older people are more likely to fall. Fall injuries amongst older people are a leading cause of death and disability. Many older people do not do regular exercise so that they lose muscle tone, strength, and flexibility which affect balance and predispose them to falls. The management of falls in residential care settings is a major concern with strategies for prevention and monitoring a focus in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
(42 reference statements)
1
55
0
2
Order By: Relevance
“…The same result was demonstrated after 8 weeks of yoga sessions in older adults [27] and in healthy young adults [28]. Improved balance function, reduced pain was detected in older individuals (n = 11) after the 14th week modified yoga program [29]. The study found that both balance and mobility benefited in the study of 54 community dwelling older individuals (n = 54) after the 12th week of twice-weekly Iyengar yoga session [30] and after the 8th week of an 80 minutes biweekly yoga program [31].…”
Section: Balancesupporting
confidence: 74%
“…The same result was demonstrated after 8 weeks of yoga sessions in older adults [27] and in healthy young adults [28]. Improved balance function, reduced pain was detected in older individuals (n = 11) after the 14th week modified yoga program [29]. The study found that both balance and mobility benefited in the study of 54 community dwelling older individuals (n = 54) after the 12th week of twice-weekly Iyengar yoga session [30] and after the 8th week of an 80 minutes biweekly yoga program [31].…”
Section: Balancesupporting
confidence: 74%
“…For example, Oken et al [13] reported that mobility measures including chair stands and timed walking performance did not improve after yoga participation in healthy seniors although enhanced lower-extremity flexibility and balance were evident. Contrastingly, no significant changes in total balance score, fear of falling, flexibility, or quality of life, were found in studies reported by Schmid et al and Saravanakumar et al [14, 15]. …”
Section: Introductionmentioning
confidence: 79%
“…The amount of information regarding program design varied greatly across these reports: some only included a list of poses [10, 11, 14]; some provided detailed information of pose progression [15, 16]; some included pose illustrations [12, 17]; others described the programs without pose details [79, 13, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Yoga was as effective as tai chi in improving balance and postural stability. In another randomized controlled trial comparing yoga and tai chi, yoga and tai chi were both effective for reducing falls, although the yoga group had a greater reduction in pain [135]. In a systematic review of balance studies, 15 studies showed positive results on at least one balance measure [136].…”
Section: Balancementioning
confidence: 98%